Data supporting the publication "Transforming wastewater ammonia to carbon free energy: Integrating fuel cell technology with ammonia stripping for direct power production" - Davey, Christopher J.; Luqmani, Benjamin A.; Thomas, Navya; McAdam, Ewan (Cranfield University, 2022)
Data File supporting article titled "Transforming ammonia to carbon free energy: Integrating fuel cell technology with ammonia stripping for direct power production"
Keywords: ammonia fuel cell'; 'Wastewater'; 'Net zero'; 'energy neutrality'; 'vacuum stripping'; 'waste heat'